Implementasi Peningkatan Karakter Religius Melalui Program Keassalaman Berdasarkan IASP 2020 - Siti Rochmah Dirgantini; Siti Hanna Qodriani; Susan Sundari; Ade Yeti Nuryanti; Mulyawan Safwandy Nugraha (Indonesia, 2023)
This research aims to find out what the greetings program is and how the implementation of the greetings program is a school effort to improve the religious character of students based on IASP 2020 in order to produce good-quality graduates who are able to be a solution to existing problems. The method used in this study is a qualitative method with a case study approach that focuses on cases of low religious character that hit students due to changes and developments in the times, namely advances in digital technology. The data collection process was based on the results of in-depth interviews, observations, and document reviews in accordance with IASP 2020. The results of this study showed that the greeting program proved to be effective in improving students' religious character, including students who are accustomed to praying before studying, 4S habituation, concern for the environment, do not force the will to embrace a particular religion, have a tolerant attitude, and live in harmony between adherents of different religions and beliefs.